STEROIDS APPLICATION IN ORAL DISEASES - K.M.K. MASTHAN; N. ARAVINDHA BABU; ABHINAV JHA; M. ELUMALAI (International Journal of Pharma and Bio Sciences, 2013)
Steroids are substances that are naturally produced in the body. Steroids are produced by the adrenal glands which are small glands lying above the kidneys. It may regulate our immune system, balance the intake of salt and water in our bodies. Steroid helps in reducing inflammation. Most common types of steroids that are used in dentistry are hydrocortisone, dexamethasone, methylprednisolone and prednisolone. In dentistry, apart from surgeries, steroids are widely used and accepted mode of treatment for oral mucosal lesions such as oral lichen planus, oral submucous fibrosis, erythema multiforme, pemphigus vulgaris, pemphigoid and mucocele. This review discusses about the steroids application in oral diseases